Oxidative modification of petroleum resins and reception of emulsions with industrial oils - Fisenko D. V. Darjya Viktorovna; Manankova A. A. Anna Anatolievna; Bondaletov V. G. Vladimir Grigoryevich; Filippova M. Y. Marina Yurjevna; Yakimova V. A. Vera Alekseevna (2016, 2016)
Title screen